Effectiveness of a Plickers-Assisted Teams Games Tournament (TGT) Model on Students’ Learning Interest in Islamic Religious Education - Kinasih, Putri Ayu; Kesuma , Guntur Cahaya; Hasanah , Uswatun (Journal of Islamic Education Research, 2026)
Students’ learning interest represents a crucial affective factor influencing engagement, persistence, and academic achievement. Nevertheless, instruction in Islamic Religious Education often remains teacher-centered and lacks interactive learning experiences, resulting in low student participation and motivation. This study examines the effectiveness of integrating the Teams Games Tournament (TGT) cooperative learning model with Plickers in enhancing students’ learning interest. A quantitative quasi-experimental method with a post-test only control group design was employed. Participants were eighth-grade students at State Junior High School 1 Jati Agung, with two intact classes randomly assigned to experimental and control groups. The experimental group received cooperative learning through structured tournaments supported by a QR code-based Plickers response system, while the control group received conventional lecture-based instruction. Data were collected using a validated and reliable 20-item learning interest questionnaire covering enjoyment, engagement, attention, and curiosity. Statistical analyses included assumption testing, independent samples t-test, and effect size estimation. Results demonstrated that the experimental group achieved substantially higher learning interest scores than the control group. The independent samples t-test revealed a significant difference, t(76) = 10.928, p < 0.001. The magnitude of the effect was very large (Cohen’s d = 2.47), indicating strong practical and educational impact. Students exposed to the intervention showed greater active participation, enthusiasm, sustained attention, and collaborative interaction during learning activities. This study contributes novelty by integrating cooperative learning with an inclusive digital response system and emphasizing affective outcomes within Islamic Religious Education. The study contributes theoretically to technology-assisted cooperative learning literature and practically provides an accessible, low-cost, and replicable instructional strategy for fostering more engaging and student-centered classrooms.